Epilepsy: exploring psychosocial aspects in a sample of clinic attenders in two black townships in Cape Town - Pefile, Lulama Lynda (Department of Psychology, 2026)
There has been a growing realisation that the social and psychological consequences of epilepsy may be more debilitating than the seizures themselves. The present dissertation utilized the framework of a sociopsychological model in trying to gain an understanding of the consequences of having epilepsy. Twenty respondents attending the epileptic clinics of two day-hospitals located in the peri-urban townships of Guguletu and Nyanga in Cape Town were interviewed with the use of a semi-structured interview schedule. The interview explored aspects in the medical management of their illness including the use of indigenous forms of health care; vocational problems faced by respondents, personal adjustment to the seizures, and interpersonal relationship problems. Few ·respondents enjoyed good control over their seizures, yet none admitted to being dissatisfied with western treatment. Even so, there was mention of supernatural causative factors in the etiology of epilepsy and most respondents had at some time during the course of their illness consulted an indigenous healer. A major finding was a high rate of unemployment in the epileptic sample with dire secondary financial consequences. Further problems associated with having epilepsy included the unpredictable and potentially dangerous nature of epileptic attacks, the adjusting of their lifestyles, the experience of limited job and educational opportunites and social rejection especially because of a belief that epilepsy is contagious. Implications of the study include the need to provide a better understanding of the medical aspects of epilepsy to patients with every effort made to assist them to attain control over their seizures. There is a need to encourage open and free dialogue about cultural beliefs on the illness and its treatment while discouraging obviously erroneous and damaging beliefs. A need for practical assistance in the form of disability grants, access to a social worker and to the services of the South African National Epilepsy League was identified.